A directionally-dependent evolutionary lagged coherency model of nonstationary horizontal spatially variable seismic ground motions for engineering purposes. Issue 117 (February 2019) - Wang, Ding; Wang, Liwei; Xu, Jun; Kong, Fan; Wang, Guobo
Abstract: A novel directionally-dependent evolutionary lagged coherency model for nonstationary horizontal spatially variable seismic ground motions is developed for engineering purposes. Evolution of the model is achieved by varying the values of the parameters in time. First, based on the generalized harmonic wavelets, the approach for estimating the evolutionary lagged coherency of realistic seismic ground motions is presented. Then, the evolutionary lagged coherency model of spatially variable seismic ground motions is formulated. This proposed model is based on the analytic form of the cross correlation function for a plane wave in a homogeneous random medium. The parameters of the model are treated as piecewise constant variables for describing the evolutionary characteristics of the estimated coherency. Finally, the evolutionary lagged coherency of the spatially variable ground motion accelerations recorded at the SMART-1 array, Taiwan, during Event 45, is investigated and modeled. The ground motions are divided into three sections: a build-up portion, a high-intensity portion and a decaying portion. The model parameters are identified in these three sections respectively. The comparisons between the actual estimated coherency and the model indicate that the proposed evolutionary lagged coherency model can well reflects the time-dependent correlation of the realistic spatially variable seismic ground motions. Highlights: A s﻿e﻿i﻿s﻿m﻿i﻿c﻿ directionally-dependent evolutionary lagged coherency model is proposed. M﻿o﻿d﻿e﻿l﻿ ﻿p﻿a﻿r﻿a﻿m﻿e﻿t﻿e﻿r﻿s are identified. Evolutionary lagged coherency is estimated via generalized harmonic wavelets.